Requirements Identification Towards a Design of Adaptive ICTs for Supporting Bipolar Disorder Treatment in Different Healthcare Contexts - Torri, Emanuele; Mayora, Oscar; Cobo, Jesus; Palao, Diego (EAI Endorsed Transactions on Pervasive Health and Technology, 2015)
This paper presents patient and caregiver perspective on ICTs supporting bipolar disorder management in multinational healthcare provisioning contexts. The envisioned mHealth solutions should adopt general requirements that could be instantiated into different clinical settings. Engagement of users in designing new technologies for mental health is crucial to ensure empowerment and patient-centeredness of services. We performed focus groups to understand user needs, attitudes and experiences towards the supportive ICTs in two target regions where the expected solutions will operate. The survey offered valuable inputs for the construction of the clinical requirements used to produce a trans-national call for tender on mobile health solutions aimed at supporting bipolar disorders treatment among public purchasers in different European countries. The study was part of the NYMHPA-MD (Next Generation Mobile Platform for Health in Mental Disorders) project, co-funded by the European Commission.
Keywords: bipolar disorder; healthcare contexts; mobile health